A modeling approach for electrokinetic transport in double-porosity media. (1st November 2022) - López-Vizcaíno, Rubén; Cabrera, Virginia; Sprocati, Riccardo; Muniruzzaman, Muhammad; Rolle, Massimo; Navarro, Vicente; Yustres, Ángel
Highlights: An approach to model electrokinetic transport in double porosity media is presented. The tool M4EKR is adapted to evaluate de electromigration in Donnan porosity. Electrostatic effects due to negative charge of the clay particles are evaluated. Transport in microstructure defines the behavior of the electrokinetic process. Abstract: Electrokinetic techniques have attracted considerable attention due to their competitive advantage in enhancing transport phenomena and remediation of low permeability soils. However, many types of low-permeability porous media, such as active clays like bentonite, present a double porosity structure that strongly affects mass transfer processes. In this work, we develop a modeling approach to simulate electrokinetic transport in double porosity media. The proposed model is based on the previously released code M4EKR and explicitly considers the transport due to electromigration as well the effects of the electrical diffuse layer in charged porous media. For this purpose, two modeling levels have been established: one associated with the soil macrostructure (bulk water) and the other with the microstructure (diffuse layer). At the latter level, the effect of the electrostatic interactions imposed by the negative charge of the clay particles is modeled with a Donnan approach. The comparison of the results between synthetic cases in single and double porosity systems shows the fundamental role of the microstructural modeling level. High enrichment of cations and, therefore, high cationic fluxes are produced in such microstructural level. These mechanisms significantly modify the extent of cation transport by electromigration and, thus, directly influence the transport of other species determined by the electrostatic interactions.